In Vitro Generation of Posterior Motor Neurons from Human Pluripotent Stem Cells. Issue 9 (21st September 2021) - Wind, Matt; Tsakiridis, Anestis
Abstract: The ability to generate spinal cord motor neurons from human pluripotent stem cells (hPSCs) is of great use for modelling motor neuron–based diseases and cell‐replacement therapies. A key step in the design of hPSC differentiation strategies aiming to produce motor neurons involves induction of the appropriate anteroposterior (A‐P) axial identity, an important factor influencing motor neuron subtype specification, functionality, and disease vulnerability. Most current protocols for induction of motor neurons from hPSCs produce predominantly cells of a mixed hindbrain/cervical axial identity marked by expression of Hox paralogous group (PG) members 1‐5, but are inefficient in generating high numbers of more posterior thoracic/lumbosacral Hox PG(8‐13) + spinal cord motor neurons. Here, we describe a protocol for efficient generation of thoracic spinal cord cells and motor neurons from hPSCs. This step‐wise protocol relies on the initial generation of a neuromesodermal‐potent axial progenitor population, which is differentiated first to produce posterior ventral spinal cord progenitors and subsequently to produce posterior motor neurons exhibiting a predominantly thoracic axial identity. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Differentiation of neuromesodermal progenitors Basic Protocol 2 : Posterior ventral spinal cord progenitor differentiation Basic Protocol 3 : Posterior motor neuron differentiation